Palaeoproteomic evidence identifies archaic hominins associated with the Chatelperronian at the Grotte du Renne - Welker, F; Hajdinjak, M; Talamo, S; Jaouen, K; Dannemann, M; David, F; Julien, M; Meyer, M; Kelso, J; Barnes, I; Brace, S; Kamminga, P; et al. (National Academy of Sciences, 2016)
In Western Europe, the Middle to Upper Paleolithic transition is associated with the disappearance of Neandertals and the spread of anatomically modern humans (AMHs). Current chronological, behavioral, and biological models of this transitional period hinge on the Châtelperronian technocomplex. At the site of the Grotte du Renne, Arcy-sur-Cure, morphological Neandertal specimens are not directly dated but are contextually associated with the Châtelperronian, which contains bone points and beads. The association between Neandertals and this“transitional”assemblage has been controversial because of the lack either of a direct hominin radiocarbon date or of molecular confirmation of the Neandertal affiliation. Here we provide further evidence for a Neandertal–Châtelperronian association at the Grotte du Renne through biomolecular and chronological analysis. We identified 28 additional hominin specimens through zooarchaeology by mass spectrometry (ZooMS) screening of morphologically uninformative bone specimens from Châtelperronian layers at the Grotte du Renne. Next, we obtain an ancient hominin bone proteome through liquid chromatography-MS/MS analysis and error-tolerant amino acid sequence analysis. Analysis of this palaeoproteome allows us to provide phylogenetic and physiological information on these ancient hominin specimens. We distinguish Late Pleistocene clades within the genus Homobased on ancient protein evidence through the identification of an archaic-derived amino acid sequence for the collagen type X, alpha-1 (COL10α1) protein. We support this by obtaining ancient mtDNA sequences, which indicate a Neandertal ancestry for these specimens. Direct accelerator mass spectometry radiocarbon dating and Bayesian modeling confirm that the hominin specimens date to the Châtelperronian at the Grotte du Renne.